2019
DOI: 10.1371/journal.pone.0215693
|View full text |Cite
|
Sign up to set email alerts
|

Role of physical performance measures for identifying functional disability among Chinese older adults: Data from the China Health and Retirement Longitudinal Study

Abstract: Background Functional disability is a common health burden in older adults and follows a hierarchical pattern. Physical performance measures are useful for the objective estimation of functional disability. This study primarily aimed to compare the validity of handgrip strength and gait speed, alone and in combination, for recognizing the functional disability among Chinese older adults. This study also aimed to stratify the functional disability according to the criterion-referenced values of han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 35 publications
6
38
0
2
Order By: Relevance
“…CHARLS used multistep probability sampling strategy, selecting 150 representative counties and 450 villages/urban communities from 28 provinces. The detailed methodology description and core questionnaire of the CHARLS have been described in previous studies [ 9 11 ]. The national baseline survey for the CHARLS began in 2011, and the respondents were followed every two years by using a face-to-face computer-assisted personal interview.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CHARLS used multistep probability sampling strategy, selecting 150 representative counties and 450 villages/urban communities from 28 provinces. The detailed methodology description and core questionnaire of the CHARLS have been described in previous studies [ 9 11 ]. The national baseline survey for the CHARLS began in 2011, and the respondents were followed every two years by using a face-to-face computer-assisted personal interview.…”
Section: Methodsmentioning
confidence: 99%
“…Every participant was measured twice for both left and right hand by holding the dynamometer at a right angle (90°) and squeezing the handle for a few seconds. Participants were asked to provide maximum effort for the measures [ 11 ]. We used the maximum available values measured twice with left and right hand, and then took the average of maximum available values.…”
Section: Methodsmentioning
confidence: 99%
“…The total score was calculated by summing the scores of all variables. Sensitivity, specificity, and the AUC were calculated at different cut-off values, and the maximal Youden index was used to identify the optimal cut-off point [46]. The Youden index was calculated as follows: sensitivity + specificity − 1.…”
Section: Clinical Scoring Toolmentioning
confidence: 99%
“…Likewise, another longitudinal study of 2270 Mexican Americans aged at least 65 years found that those who were considered weak had a 1.25 higher hazard (p < 0.0001) for incident BADL disability compared to persons who were not weak and did not have diabetes over a 19-year study period. 71 Zhang et al 72 examined the association between weakness and BADL disability in 6127 Chinese adults aged at least 45 years and found that those who were considered weak had 2.26 greater odds (p < 0.001) for BADL disability compared to those who were not weak. McGrath et al 73 investigated the association between HGS and individual BADLs in 17,747 Americans aged at least 50 years during an 8-year study period and found every 5-kg decrease in HGS was associated with a 1.20 higher hazard for an eating limitation, 1.14 higher hazard for a walking limitation, 1.14 higher hazard for a bathing limitation, 1.09 higher hazard for a dressing limitation, 1.08 higher hazard for a transferring limitation, and 1.06 higher hazard for a toileting limitation (p < 0.05 for all).…”
Section: Hgs and Functional Disabilitymentioning
confidence: 99%